2018
DOI: 10.1093/jeg/lby011
|View full text |Cite
|
Sign up to set email alerts
|

Separate Worlds? Explaining the current wave of regional economic polarization

Abstract: Interregional and inter-metropolitan economic divergence is greater in many western developed countries than it has been in many decades. Divergence manifests itself in many ways, including per capita income, labor force participation, and the spatial the distribution of skills and returns to education. At the same time, geographical polarization of political preferences and electoral choices has increased, with gains in populism and nationalism in some regions, and broadening of socially liberal, pro-trade, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 86 publications
6
75
0
2
Order By: Relevance
“…Finally, echoed in Storper's () and Iammarino et al's () findings, we discover that the distinct geographies of employment, FDI, and trade give rise to regional convergence (or divergence) in China. Among cities and regions, the benefits of agglomeration across China resemble those found in the USA—where most of the innovation and technology firms geographically cluster within big metropolitan regions (Moretti, ; Porter, )—but differ from those in the European Union, in which many industrial sectors are spreading out and the effect of history remains strong (Storper, Chen & De Paolis, ).…”
Section: Analyses and Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Finally, echoed in Storper's () and Iammarino et al's () findings, we discover that the distinct geographies of employment, FDI, and trade give rise to regional convergence (or divergence) in China. Among cities and regions, the benefits of agglomeration across China resemble those found in the USA—where most of the innovation and technology firms geographically cluster within big metropolitan regions (Moretti, ; Porter, )—but differ from those in the European Union, in which many industrial sectors are spreading out and the effect of history remains strong (Storper, Chen & De Paolis, ).…”
Section: Analyses and Discussionsupporting
confidence: 77%
“…These case studies can help us determine the applicability of those theories for other developing countries. That is, many countries in the Global South demand solutions for the harms of regional inequality (Martin, Tyler, Storper, Evenhuis, & Glasmeier, ; Storper, ), so these experiences may provide some solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metropolitan regions also host a broad variety of organisations in the knowledge application and exploitation subsystem, including firms in sectors traditionally linked to university research (Storper, 2018). In addition, these regions are typically well endowed with major communication infrastructures such as ports and airports, ensuring their connectedness to global knowledge networks (McCann, 2008;Rodríguez-Pose & Fitjar, 2013).…”
Section: David Fernández Guerreromentioning
confidence: 99%
“…Economic geographers have only begun recently to pay attention to the issue in the context of urban development (Florida et al ; Kemeny & Cooke ). While these studies have concluded that larger cities tend to host more skilled workers and pay higher wages, Storper () rightly pointed out the story of United States’ regional development in the last fifty years has remained focus on regional divergence arising from relocation of the skilled from the Rustbelt to the Sunbelt.…”
Section: Introductionmentioning
confidence: 99%